The vulnerability of GPS spoofing - Wong, Wei Jie (2019)
In the 20th century, the knowledge of detecting location and time began to gain significance. Research was undergone in the study of the Global Positioning System (GPS) in order to gain such knowledge, leading to many technological advancements incorporating GPS in today’s context. However, this advancement also led to the rise of GPS spoofing attacks for many purposes such as trespassing of restricted areas, denial of services, collection of confidential information or personal financial gains. This thesis revolves around the understand of GPS spoofing and its function.